Engineering the complex SOC : fast, flexible design with configurable processors. - Rowen, Chris, ....-; Leibson, Steve, ....- (Upper Saddle River : Prentice Hall, 2004)
This book outlines a new, essential methodology for developing SoC hardware and software using configurable, extensible processor technology as a unifying theme. In addition to laying out a dramatically new SOC design methodology, the book introduces the concepts of processor configuration, extension, hardware/software co-generation and multiple processor partitioning and communication. It uses real-world examples extensively, both in the form of case studies about architecture decisions and in very short examples that communicate the flavor and the power of these methods. No other book discusses how to use multiple processors on a single chip to speed the chip design process and achieve faster performance. All other books that cover SoC design assume the traditional 1980's-style approach to system design that employs one central processor or, at most, one processor and a co-processor such as a digital signal processor (DSP) on a chip. Other books assume that if there are parts of the design that can't be run fast enough on the main system processor, then the designer must hand-code those parts of the design in hardware-description language (HDL) such as Verilog or VHDL. That was state-of-the-art thinking for chip design in the early 1990s, but as chip complexity increased and configurable, embedded processor cores were introduced and established, SoCs with multiple processors are proving to be an effective alternative.
Keywords: Geïntegreerde schakelingen; Microprocessoren